Topography and seasonality promotes taxonomic beta diversity of seedlings in a tropical wetland - Bao, Francielli [UNESP]; Villa, Pedro Manuel; Rodrigues, Alice Cristina; Schmitz, Daniela; de Assis, Marco Antonio [UNESP]; Arruda, Rafael; Pott, Arnildo (Oecologia Australis, 2019)
Spatial and temporal beta diversity of seedlings in tropical wetland remain poorly understood. We assessed the ecological pattern of taxonomic beta diversity of seedling assemblages along a topographic gradient, seasonally flooded disturbance, and sampling years in a tropical wetland. We tested that seasonally flooded disturbance on seedling assemblage promotes a high taxonomic beta diversity due to a high taxonomic turnover along the topographical gradient. Here we examined a large database from 200 plots (each having 0.5 × 0.5 m), across eight seasonally flooded grasslands in the Pantanal of central-west Brazil. We selected data on ponds for four years at two characteristic hydrological phases per year: post-flood (July and August), and post-dry season (October and November). We classified the topographical gradient into three levels 1) low—longer duration of flood; 2) mid—intermediate level; and 3) high—short duration of flood (dry soil). For both post-flood and post-dry seasons, we counted the number of seedlings within five plots at each topographic level. Additionally, taxonomic beta diversity was examined via novel abundance-based metrics (including both turnover and nestedness patterns). Overall, taxonomic beta diversity was consistently higher in high topographic level and post-dry season plots. We observed differences in beta diversity components between topographical levels, seasons and years. Topographical gradient and seasonally flooded promotes more variation in taxonomic turnover and beta diversity; due to these environmental filters we presume that the resulting beta diversity can be decisive in the species diversity in this tropical wetland.
Keywords: Flood disturbance; Nestedness-resultant component; Taxonomic turnover; Topographical gradient